CD14- CD16+ monocyte PD-L1 prevents early tuberculosis progression and constrains reactivation under immune checkpoint therapy - Wang, Wentao; Liu, Chenyang; Wu, Wenxaio; Yi, Zhengjun; Shen, Jie (Frontiers in Cellular and Infection Microbiology, 2025)
Immune checkpoint blockade (ICB) has revolutionized cancer therapy, yet its unintended impact on chronic infections remains poorly understood. Here, we identify PD-L1 expression on CD14- CD16+ monocytes as a critical determinant for preventing early tuberculosis (TB) progression. By integrating real-world adverse event data, Mendelian randomization (MR), and transcriptomic analysis, we establish a causal and cell-specific link between PD-L1 downregulation and early TB progression. Analysis of the FAERS database revealed that the PD-L1 inhibitor durvalumab is significantly associated with TB-related adverse events (reporting odds ratio = 7.81; 95% CI: 4.43-13.78; P = 1.10×10-18). MR analysis confirmed that genetically elevated PD-L1 expression in CD14- CD16+ monocytes confers protection against early TB progression (OR = 0.918, P = 0.042), independent of confounding or reverse causality. Transcriptomic profiling revealed that PD-L1high CD14- CD16+ monocytes exhibit enhanced antigen surveillance, whereas PD-L1low cells display metabolic reprogramming associated with immune escape. Upstream regulatory analysis identified CDAN1, TCOF1, and LMO2 as transcriptional drivers of PD-L1, enriched in high-risk individuals. In silico drug prediction and molecular docking suggested several PD-L1-modulating compounds, including ruthenium, pomalidomide, zidovudine, and lycorine. Notably, several of these compounds (e.g., ruthenium complexes, pomalidomide, aziridine) have reported anti-mycobacterial effects, which supports the reliability of our screening results and their potential relevance to TB regulation. In vitro validation demonstrated that lycorine dose-dependently upregulates PD-L1 and inhibits Mycobacterium tuberculosis reactivation. Together, our findings define a mechanistic axis in CD14- CD16+ monocytes that underpins early TB control and is vulnerable to PD-L1 blockade. Collectively, these findings align with the established notion that assessing latent tuberculosis infection before initiating immune-modulating therapies is essential for minimizing reactivation risk, and propose tractable molecular targets for preventing TB reactivation in immunocompromised hosts.